Ionic‐Liquid‐Based Safe Adjuvants. Issue 46 (15th October 2020) - Ukidve, Anvay; Cu, Katharina; Goetz, Morgan; Angsantikul, Pavimol; Curreri, Alexander; Tanner, Eden E. L.; Lahann, Joerg; Mitragotri, Samir
Abstract: Adjuvants play a critical role in the design and development of novel vaccines. Despite extensive research, only a handful of vaccine adjuvants have been approved for human use. Currently used adjuvants are mostly composed of components that are non‐native to the human body, such as aluminum salt, bacterial lipids, or foreign genomic material. Here, a new ionic‐liquid‐based adjuvant is explored, synthesized using two metabolites of the body, choline and lactic acid (ChoLa). ChoLa distributes the antigen efficiently upon injection, maintains antigen integrity, enhances immune infiltration at the injection site, and leads to a potent immune response against the antigen. Thus, it can serve as a promising safe adjuvant platform that can help to protect against pandemics and future infectious threats. Abstract : Despite extensive research, only a handful of vaccine adjuvants, non‐native to the human body, have been approved. A new adjuvant based on ionic liquids is demonstrated, which combines two metabolites of the body, choline and lactic acid (ChoLa). It successfully enhances immune infiltration at the injection site and leads to a potent immune response against the antigen, serving as a safe adjuvant alternative that can help protect against infections.